PROFIL KECERDASAN EMOSIONAL SISWA DI SMK KIMIA DHARMA BHAKTI - Mercy Firda Rizki Iriyanti; Siti Fatimah; Muhammad Rezza Septian (IKIP Siliwangi, 2022)
Emotional intelligence is needed by students to face, change and strengthen unpleasant conditions to be natural to face. The components contained in emotional intelligence are: self-awareness, controlling emotions, self-motivation, empathy and social relationships. The purpose of this study was to determine the profile of students' emotional intelligence at SMK Kimia Dharma Bhakti. The method used in this research is descriptive quantitative. The sample of this research is 100 students of SMK Kimia Dharma Bhakti. The data collection procedure uses a 24 item emotional intelligence questionnaire. Analysis and processing of emotional intelligence data with the Exel program from Microsoft office, and based on the results of the study show that not all of them have high emotional intelligence. It is proven by the results of the emotional intelligence questionnaire, there are only 18 people who have emotional intelligence in the high category with a percentage of 18%, while 69 people in the medium category with a proportion of 69%, and 13 people in the low category with a percentage of 13%.Keywords: Emotional Intelligence, student